Ответы и объяснения

  • IOriOnI
  • почетный грамотей
2012-05-22T18:51:17+04:00

1.  (3x^2-xy+2y^2) + (7x^2+xy-1) = 10x^2+2y^2-1

2. (2a^2+a-3)-(3a^2+a-5) = -a^2+2

3. (5m^2-5m+3)+(-4m^2-5m-3) =m^2-10m

4. (2a-3b+4c)*(-3x) = -6ax+9bx-12cx

5. (2y^6+6)* 6y^15 = 12y^21+36y^15

6. (2x-1)*(4x-3) = 8x^2-6x-4x+3 = 8x^2-10x+3

7. (a+b^2)*(b^2+a) = ab^2+a^2+b^4+ab^2 = 2ab^2+a^2+b^4

8. 6x(x-3) -x(2-x) = 6x^2-18x-2x+x^2 = 7x^2-20x

9. 2x(x+5) -(2x-1)*(4+x) = 2x^2+10x-(8x+2x^2-4-x) = 3x+4

10. 3x(2x-1)-6x(7+x)=90

6x^2-3x-42x-6x^2=90

-45x = 90

x= -2

11. 24x-6x(13x-9) = -13-13x(6x-1)

24x-78x^2+54x = -13-78x^2+13x

65x= -13

x= -0,2